Voxyvi: A system for long-term audio and video acquisitions in neonatal intensive care units. (February 2021) - Cabon, S.; Porée, F.; Cuffel, G.; Rosec, O.; Geslin, F.; Pladys, P.; Simon, A.; Carrault, G.
Abstract: Background: In the European Union, 300, 000 newborn babies are born prematurely every year. Their care is ensured in Neonatal Intensive Care Units (NICU) where vital signs are constantly monitored. In addition, other descriptors such as motion, facial and vocal activities have been shown to be essential to assess neurobehavioral development. Aim: In the scope of the European project Digi-NewB, we aimed to develop and evaluate a new audio-video device designed to non-invasively acquire multi-modal data (audio, video and thermal images), while fitting the wide variety of bedding environment in NICU. Methods: Firstly, a multimodal system and associated software and guidelines to collect data in neonatal intensive care unit were proposed. Secondly, methods for post-evaluation of the acquisition phase were developed, including the study of clinician feedback and a qualitative analysis of the data. Results: The deployment of 19 acquisition devices in six French hospitals allowed to record more than 500 newborns of different gestational and postmenstrual ages. After the acquisition phase, clinical feedback was mostly positive. In addition, quality of more than 300 recordings was inspected and showed that 77% of the data is exploitable. In depth, the percentage of sole presence of the newborn was estimated at 62% within recordings. Conclusions: This study demonstrates that audio-video acquisitions are feasible on a large scale in real life in NICU. The experience also allowed us to make a clear observation of the requirements and challenges that will have to be overcome in order to set up audio-video monitoring methods. Highlights: Audio and video analyses are essential to assess the maturation of preterm infants. Published works were mainly performed under controlled conditions. A new audio-video system was designed and integrated in six hospitals. Long term recordings of more than 500 newborns were performed under real conditions. Solutions to integrate audio-video monitoring in NICU are discussed in this paper.